PERENCANAAN UNIT BANGUNAN PENGOLAHAN AIR BUANGAN KAMPUS UKRI MENGGUNAKAN BIOFILTER AEROB - Erika Herliana (Prodi Arsitektur UNIVERSITAS KEBANGSAAN, 2024)
In recent years, Universitas Kebangsaan Republik Indonesia (UKRI) has experienced rapid growth in the education sector, facilities, as well as an increasing number of students and staff. Along with this development, the volume of wastewater produced has also seen significant increase. If not managed efficiently, this wastewater can pose a threat to the surrounding environmental quality and potentially become a source of public health issues. Therefore, efforts to improve sanitation are required, such as the installation planning of domestic wastewater treatment facilities at the UKRI campus. Wastewater treatment through the aerobic biofilter method is one system that employs biological processes, consisting of media that serve as a habitat for submerged microorganisms, supplemented with an aeration system. The chosen domestic wastewater treatment installation in the UKRI campus is the aerobic biofilter. The planning for the selection of this installation is based on land requirements, construction, operation, maintenance, investment costs, and efficiency. The calculated wastewater flow rate is 57.6 m3/day. The aerobic biofilter produces effluent with concentrations of temperature 28 ºC; pH 7.5; TSS 18.69 mg/L; COD 73.64 mg/L; BOD 37.66 mg/L. The construction of the aerobic biofilter consists of fiber and concrete materials with dimensions of 5 m in length, 0.6 m in width, and 1.5 m in height. Keyword: wastewater treatment, biofilter aerob, UKRI campus